Legal protection against curators as a result of the dualism bankruptcy decisions for same debtor (Analysis of Commercial Court Decision at Surabaya District Court Number 08/Pdt.Sus - Other Lawsuits/2018/PN-Niaga.Sby. Jo. Number 02/Pdt.Sus-PKPU/2017/PN.Niaga.Sby. Date July 16, 2018) - Albert Riyadi Suwono; Made Warka; Krisnadi Nasution; Suratman (Technium Social Sciences Journal, 2024)
Bankruptcy is a condition of debtor’s failure to pay his debts to his creditors. The debtor’s failure to pay debts continuously will result in the debtor’s bankruptcy. One of the legal instruments that can be used to settle debts as debtor’s obligation. Historically, the presence of bankruptcy institutions in Indonesia since Dutch East Indies government in Indonesia, which was enacted known as Faillissements verordening, Staatsblad 1905:217 juncto Staatsblad 1906:348), which was later referred to as the Bankruptcy Law. However, in its development, the substance of Faillissements verordening was considered no longer in accordance with development and legal needs of today’s society. Therefore, the Faillissements verordening has been amended by Government Regulation in Lieu of Law Number 1 of 1998 concerning Amendments to Law on Bankruptcy, which was then stipulated as a Law based on Law Number 4 of 1998 concerning Bankruptcy. However, these changes to law have not been able to meet the developments and legal needs of society.